PENDIDIKAN ISLAM DALAM MENJAWAB PROBLEM ETIKA BERMEDIA SOSIAL, CYBER BULLYING, HOAKS, DAN KONTEN NEGATIF - Farichah, Eneng; Nasaruddin, Nasaruddin (LP2M STAI Darul Kamal NW Kembang Kerang, 2024)
Technological developments have brought positive impacts as well as ethical challenges, especially for the younger generation in using social media. The phenomena of cyber bullying, the spread of hoaxes, hate speech, and negative content have become serious issues that require comprehensive solutions. This study aims to examine how Islamic education plays a role in addressing ethical issues in social media. The research method used is a literature review with a normative and contextual approach. The results show that Islamic values, such as tabayyun (clarification of information), mujahadah al-nafs (self-control), and the principle of ukhuwah (brotherhood), are relevant to be applied in facing digital challenges. Additionally, the integration of Islamic-based digital literacy into the education curriculum can equip students with practical skills and a moral foundation for using social media. However, the implementation of Islamic Education as a solution to digital ethics still faces obstacles, such as the lack of digital literacy material in the curriculum, the suboptimal role of teachers as role models for digital communication, and weak parental guidance. Therefore, it is necessary to strengthen the curriculum, increase teacher capacity, and create synergy between schools, families, and communities to build a healthy and ethical digital ecosystem